Health Education to Improve Maternal Awareness on Soy-Based Infant Formula for Individuals with Cow’s Milk Allergy in Indonesia - Setiabudiawan, Budi; Surapsari, Juwalita; Kartjito, Melissa Stephanie; Sitorus, Nova; Dilantika, Charisma; Basrowi, Ray Wagiu; Jo, Juandy (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
Background: Cow’s milk allergy is relatively common among Indonesian infantswho are not exclusively breastfed. Despite extensive hydrolyzed formula and aminoacid-based formula are the recommended nutrition for infants with moderate-tosevere illness, not all parents could provide those specialized formulas, presumablydue to the high cost, low availability and poor palatability. In that case, soy-basedinfant formula could be an alternative nutrition. However, it was unknown whetherIndonesian mothers were aware on that alternative nutrition. Objective: We therefore assessed the knowledge levels of mothers who participated in an online platform of PrimaKu on the usefulness of soy-based infant formula to support growthand development of children with cow’s milk allergy. Methods: The study subjectsappeared to have sufficient levels of knowledge on the usefulness of soy-based infant formula for children with cow’s milk allergy. Results: In addition, by increasing their knowledge on iron and fiber fortification in soy-based infant formula, e.g.,through regular academic presentations, mothers could be more selective in choosing alternative nutrition for children with cow’s milk allergy. Conclusion: Our studysuggested that Indonesian mothers who were active in the online platform of Primaku had sufficient levels of knowledge on the usefulness of soy-based protein formanaging children with cow’s milk allergy.